If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3e + 1 = e + 1 Reorder the terms: 1 + 3e = e + 1 Reorder the terms: 1 + 3e = 1 + e Add '-1' to each side of the equation. 1 + -1 + 3e = 1 + -1 + e Combine like terms: 1 + -1 = 0 0 + 3e = 1 + -1 + e 3e = 1 + -1 + e Combine like terms: 1 + -1 = 0 3e = 0 + e 3e = e Solving 3e = e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-1e' to each side of the equation. 3e + -1e = e + -1e Combine like terms: 3e + -1e = 2e 2e = e + -1e Combine like terms: e + -1e = 0 2e = 0 Divide each side by '2'. e = 0 Simplifying e = 0
| 2x+3=9x-1+x | | 2m+5=25+6m | | 7.2=y-6 | | 4x+17=4-7x | | 1/4h+9=-1/2h-11 | | 7.41=n-9.59 | | (3*62)-25+n=166 | | (2x+3)(3x+7)=0 | | 7x-13=2x-3 | | y=4x+160 | | 12x+10y=202 | | 3x+20=8-x | | -80=4x-16+4 | | 5/6p=20 | | f/-7-8=2 | | 11x-7=5x-13 | | 5z+5=2(8z-3) | | 22-3x=4x | | 4y-4=7(y-1) | | x(x-0.05)=300 | | -10+4w+6=-2w+23-3w | | 1b+2=-3b | | -10+4w+6=-23-3w | | 12/8x=7/10 | | 7a-4=4a+19 | | 9x^4-8x^2= | | 3x-11/4=-2x | | 3(5b-2)+2=26 | | 8a+3a+18=8+7a+6 | | 4=5/w-2 | | -1/9x=-3/4 | | -1=-3z+20 |